1999
DOI: 10.1046/j.1460-9568.1999.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a reduced opioid response in interleukin‐6 knock out mice

Abstract: Cytokines are known to influence neuronal functions. The purpose of this study was to investigate the putative role of the cytokine interleukin-6 (IL-6) in the pathways involved in opioid-mediated responses, by using IL-6-deficient mice. We reported that with a thermal stimulus IL-6-knock-out (IL-6KO) mice presented nociceptive thresholds similar to those measured in their controls. However, they showed a reduced analgesic response both to the restraint stress and to the administration of low doses of morphine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 55 publications
2
38
0
1
Order By: Relevance
“…In IL-6 knockout mice, reduced morphine analgesia and early development of morphine tolerance were observed (Bianchi et al, 1999). IL-6 knockout mice used in that study showed increases in b-endorphin levels and decreases in m-opioid receptor densities in certain brain regions compared to that of wildtype mice (Bianchi et al, 1999). This suggests that an altered opioid system in these animals could be responsible for differences in morphine actions compared to that of wildtype animals.…”
Section: Opioid and Cytokine Interactionsmentioning
confidence: 77%
See 1 more Smart Citation
“…In IL-6 knockout mice, reduced morphine analgesia and early development of morphine tolerance were observed (Bianchi et al, 1999). IL-6 knockout mice used in that study showed increases in b-endorphin levels and decreases in m-opioid receptor densities in certain brain regions compared to that of wildtype mice (Bianchi et al, 1999). This suggests that an altered opioid system in these animals could be responsible for differences in morphine actions compared to that of wildtype animals.…”
Section: Opioid and Cytokine Interactionsmentioning
confidence: 77%
“…Alternatively, the role of IL-6 in modulating morphine actions is unclear. In IL-6 knockout mice, reduced morphine analgesia and early development of morphine tolerance were observed (Bianchi et al, 1999). IL-6 knockout mice used in that study showed increases in b-endorphin levels and decreases in m-opioid receptor densities in certain brain regions compared to that of wildtype mice (Bianchi et al, 1999).…”
Section: Opioid and Cytokine Interactionsmentioning
confidence: 83%
“…Bianchi et al (1999) revealed that the analgesic effect was reduced in IL-6 knockout mice, and IL-6 deficient mice produced tolerance to analgesic drugs. Our data also indicate a correlation between IL-6 genotype and pain in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports demonstrating that the cytokine IL-6 acts at the site of inflammation on resident and circulating immune cells to cause the release of endogenous opioids, which subsequently activate peripheral opioid receptors to produce analgesia (12,13). Whether the antinociceptive activity of AG490 is mediated by release of endogenous …”
Section: Discussionmentioning
confidence: 99%
“…The antinociceptive activity of AG490 was evaluated using this model. Previous studies have shown that IL-6 reduces hyperalgesia by increasing spinal µ-opioid receptor during chronic inflammation (10,11) and also releases opioid peptides from immune cells (12,13). Therefore, whether the antinociceptive activity of AG490 involves the opioid system at peripheral site was also investigated.…”
Section: Introductionmentioning
confidence: 99%